На пруду Ижевском: стихи / Владимир Тяптин - Тяптин Владимир Яковлевич (Удмуртия, 1993)
Экземпляры: кр (20220520) / Инвентарный номер: 27321 / Цена: / Авт.знак: Т 99 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Удм)6-5